Both movements and breeding performance are affected by individual experience in the Bonelli's eagle Aquila fasciata - Lise Viollat; Alexandre Millon; Cécile Ponchon; Alain Ravayrol; Thibaut Couturier; Aurélien Besnard (Ecology and Evolution)
Abstract Movement is a key behaviour to better understand how individuals respond to their environment. Movement behaviours are affected by both extrinsic factors that individuals face, such as weather conditions, and intrinsic factors, such as sex and experience. Because of the energy costs it entails, movement behaviours can have direct consequences on an individual's demographic parameters—and ultimately on population dynamics. However, the relationship between extrinsic factors, intrinsic factors, daily movement behaviour and demographic parameters such as breeding performance is poorly known, in particular for central place forager territorial species. We investigated here the link between movement behaviours and breeding performance of the French population of Bonelli's eagle (Aquila fasciata), a territorial and sedentary long‐lived raptor, and how this link may depend on extrinsic and intrinsic factors. By using data from annual monitoring of breeding performance for the population and GPS tracking of 48 individuals (26 males and 22 females), we found that the breeding performance of this population was mainly driven by whether a new individual was recruited into the territory, and only slightly by weather conditions. Movement behaviours (proportion of time in flight, range of movement and straightness of trajectories) showed large between‐individual variation. Those behaviours were related with weather conditions (wind and rainfall) at a daily scale, as well as with individual's experience. We found only one significant correlation between movements and breeding performance: male Bonelli's eagles spending more time flying during chick‐rearing phase had lower productivity. Movement behaviours and breeding performance were also indirectly linked through individual's experience, with more experienced birds having better breeding success and a shorter range of movement and spent less time in flight. This suggests that experienced individuals progressively acquire knowledge of their breeding territory, are more efficient in finding prey, and adapt their foraging strategies to weather conditions to minimise energy costs, allowing them higher breeding performance.